The synergy of human resources management between the regional governments of the Riau Islands Province with elements of defense in facing non military threats - Saptono, Edy; Sudarya, Agus; Pudjiatmoko, Siswo (Technium Social Sciences Journal, 2022)
Law of the Republic of Indonesia Number 3 of 2002 concerning the National Defense explained that Indonesia’s defense was carried out with a universal defense system to deal with every form of military and non-military threats. Geographically, Riau Islands Province is an area directly border to neighboring countries that have potential non-military threats. These non-military threats include illegal activities in the form smuggling of goods, illegal drugs, human trafficking, terrorism and penetration of foreign ideologies as well as cases of actual non-military threats, COVID-19 pandemic. The aims of the research are to analyze the management of human resources and the synergy between local governments and defense elements from the army, navy and air force in the Riau Islands Province as well as analyze the obstacles and the efforts to create in the face of non-military threats. The method of the research is a qualitative method with primary data collecting techniques, interviews, and secondary data in the form of literature studies. The results showed that the local government and elements of defense in the Riau Islands Province in facing non-military threats with ideological, economical, technological and information dimensions, economics, health and safety made programs by managing human resources through the functions of planning, organizing, actuating and controling. While synergy is built in two ways, namely communication through social communication through discussion, dialogue, official letters, mutual cooperation and coordination through communication forums of regional leaders. Constraints faced are geographical conditions, facilities and infrastructure, budget constraints and limited personnel. Efforts to overcome obstacles in creating synergy are increasing the frequency of regional leadership communication forums, optimizing cooperation, transforming defense human resources and increasing joint activities.